2023
DOI: 10.1021/acs.jpclett.3c01214
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Underexplored and Untapped Regions in the Chemical Space of Transition Metal Complexes

Abstract: We survey more than 240 000 crystallized mononuclear transition metal complexes (TMCs) to identify trends in preferred geometric structure and metal coordination. While we observe that an increased level of d filling correlates with a lower coordination number preference, we note exceptions, and we observe undersampling of 4d/5d transition metals and 3p-coordinating ligands. For the one-third of mononuclear TMCs that are octahedral, analysis of the 67 symmetry classes of their ligand environments reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Analysis by Kulik based on > 240 000 mononuclear complexes in the Cambridge Structural Database (CSD) showed that approximately one third of them are octahedral and often contain monodentate ligands which can dissociate to leave empty coordination sites for catalysis. [47] Thus, the authors proceeded with a design of square-planar tetradentate ligands, leaving two coordination sites for labile monodentate ligands. This went against conventional mechanistic understanding of metal catalysed coupling reactions.…”
Section: Automated Exploration Of Ligand Spacementioning
confidence: 99%
“…Analysis by Kulik based on > 240 000 mononuclear complexes in the Cambridge Structural Database (CSD) showed that approximately one third of them are octahedral and often contain monodentate ligands which can dissociate to leave empty coordination sites for catalysis. [47] Thus, the authors proceeded with a design of square-planar tetradentate ligands, leaving two coordination sites for labile monodentate ligands. This went against conventional mechanistic understanding of metal catalysed coupling reactions.…”
Section: Automated Exploration Of Ligand Spacementioning
confidence: 99%
“…Computational exploration of transition metal chemical space is, or at least is expected to be, a key part of the rational development of new catalysts and advanced functional materials with promising optical, sensing, and magnetic properties. Progress in development of computational and data-driven tools for transition metal complexes (TMCs) has considerably facilitated such research. Special note must be made of the recently introduced xTB software supporting molecular mechanics and semiempirical methods, which provide robust and powerful toolsets for quick geometry preoptimization of TMCs, and fast highly accurate post-Hartree–Fock methods such as DPLNO-CCSD­(T), allowing the complex electronic structure problems of the TMC chemistry that are inaccessible to conventional DFT calculations to be rationalized. , The transition toward automated in silico TMC exploration and analysis has been greatly facilitated by the introduction of reliable three-dimensional (3D) structure generation tools, which partially or completely automate the construction of starting molecular models. …”
Section: Introductionmentioning
confidence: 99%
“…■ METHOD Data Set. Nandy and co-workers 43 reported a comprehensive data set which includes more than 240,000 crystallized mononuclear transition metal complexes (TMCs) from The Cambridge Structural Database (CSD). 44 We followed their procedure 30 to curate "computation-ready" complexes, i.e., both oxidation states and charges are already specified upon uploading without hydrogen atoms missing in the structures.…”
Section: ■ Introductionmentioning
confidence: 99%